Innovative strategies for accelerated human resource development in South Asia teacher professional development special focus on Bangladesh, Nepal, and Sri Lanka. (Innovative strategies for accelerated human resource development series., 2017)
Significant investments have been made to modernize and improve the provision of education services. Strengthening teacher development has been a key component of these investments. However, programs on teacher development have provided mixed results. This report adopts a 360 degree perspective to review the current status of teacher development, demand and supply, and performance management in five countries from the South Asia region including Bangladesh, Nepal, and Sri Lanka, with limited reference to Bhutan and Maldives. It probes beyond teacher in service training and teacher job conditions, and investigates systemic and structural issues. Continued investment may not be the best option to improve the quality and supply of teachers, and so the challenge is how to leverage resources to meet the demand.